Sumerians in Light of Eliade’s Concept of Sacredness - Yeşim Dilek (Darulfunun Ilahiyat)
One of the most important phenomena that constituted the thought, religion, social, and cultural structure of antiquity was ab-origina, which includes concepts such as the prototype of everything being in the past, doing everything as it was done in the past, and doing everything because it was done in the past, and this phenomenon pushed the people of antiquity to create a society that stood against difference and change. As Eliade emphasizes, that truth can only be gained by practice or involvement because an object or activity only becomes genuine when it imitates or replicates an archetype. The replication of models created by divine action at a legendary beginning time is essential to human behavior in a mythologically-based world, and this is commonly denoted by the phrases “in illo tempore” or “ab origina.” Sumerians, who created a brilliant culture in ancient Mesopotamia, were unique and personified people who experienced ab-origina and manifested divinity in their people. The aim of this study is to interpret the sacredness Sumerian society in terms of Eliade’s perception.